2018
DOI: 10.1111/cge.13170
|View full text |Cite
|
Sign up to set email alerts
|

Variants in CIB2 cause DFNB48 and not USH1J

Abstract: The genetic, mutational and phenotypic spectrum of deafness-causing genes shows great diversity and pleiotropy. The best examples are the group of genes, which when mutated can either cause non-syndromic hearing loss (NSHL) or the most common dual sensory impairment, Usher syndrome (USH). Variants in the CIB2 gene have been previously reported to cause hearing loss at the DFNB48 locus and deaf-blindness at the USH1J locus. In this study, we characterize the phenotypic spectrum in a multiethnic cohort with auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…In this work, we present a thorough characterization of two variants of human CIB2, namely the WT form and the E64D mutant associated with USH1J. It should be reported that a recent study disqualified CIB2 as a USH1J-related gene, however the E64D variant was found to be associated with autosomal recessive non-syndromic hearing loss (Booth et al, 2018 ). Our biochemical and biophysical study highlights a number of clear structural and functional differences with CIB1, which may thus pose the molecular basis for understanding the malfunctioning of CIB2 in USH1J and possibly other genetic diseases causing hearing loss.…”
Section: Discussionmentioning
confidence: 94%
“…In this work, we present a thorough characterization of two variants of human CIB2, namely the WT form and the E64D mutant associated with USH1J. It should be reported that a recent study disqualified CIB2 as a USH1J-related gene, however the E64D variant was found to be associated with autosomal recessive non-syndromic hearing loss (Booth et al, 2018 ). Our biochemical and biophysical study highlights a number of clear structural and functional differences with CIB1, which may thus pose the molecular basis for understanding the malfunctioning of CIB2 in USH1J and possibly other genetic diseases causing hearing loss.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, patients with GJB 2 genetic variants present excellent outcomes in speech perception/production skills after cochlear implantation [ 35 , 36 , 37 ]. Therefore, correct interpretation of the phenotypic consequences of genetic variants is crucial in genetic diagnosis, since discrepancies in sequence variant interpretation and classification has been reported to lead to serious impact in patient health maintenance [ 38 , 39 , 40 ]. Thus, the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) has developed guidelines for clinical interpretation of genetic variants [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The p.E64D missense mutation that is thought to cause USH1J is only two amino acids away from the p.R66W missense mutation that is exclusively linked to non-syndromic deafness (Seco et al, 2016). In addition, none of the 13 patients in a multi-ethnic cohort (Booth et al, 2018) had an abnormal retinal phenotype, regardless of the mutation type, even null alleles. Lastly, while a retinal phenotype is rarely evident in mouse models of any USH type, many do exhibit some vestibular dysfunction, unlike CIB2 knockout mice (Giese et al, 2017;Michel et al, 2017).…”
Section: Mutationsmentioning
confidence: 97%